Cold ice in the ablation zone: Its relation to glacier hydrology and ice water content. Issue 2 (21st May 2013) - Ryser, C.; Lüthi, M.; Blindow, N.; Suckro, S.; Funk, M.; Bauder, A.
Abstract: [1] Cold ice within a polythermal ice body controls its flow dynamics through the temperature dependence of viscosity, and affects glacier hydrology by blocking water flow paths. Lakes on the surface, linked by persistent, deeply incised meltwater streams, are hallmark features of cold ice in the ablation zone of a glacier or ice sheet. Ice radar is a convenient method to map scattering from internal water bodies present in ice at the pressure melting temperature (PMT). Consequently, lack of internal scatters is indicative of cold ice. We use a helicopter‐borne 30 MHz ice radar to delineate the extent of cold ice within Grenzgletscher (Zermatt, Swiss Alps). The inferred thermal structure is validated with temperature measurements in 15 deep boreholes, showing excellent agreement. The cold ice occupies 80–90 % of the total ice thickness in a 400 m wide flow band along the central flow line. Quantitative interpretation of ice radar scattering power indicates a decrease of ice water content between PMT and 0.5 K below PMT, as predicted by theory, and observed in the laboratory. The cold ice which emerges at the surface in the lower ablation zone is impermeable to water, and is thus devoid of moulins if not crevassed. The surface water from melt and rain is routed through deeply incised, persistent streams and lakes, and cryoconite holes are frequent, in stark contrast to the adjacent temperate ice from other tributaries. The cold ice thus has a strong control on glacier hydrology, but is likely to change due to continued warming. Key Points: delineation of cold ice by ice radar is validated by temperature measurements radar‐determined (in situ‐)water content corroborates laboratory experiments cold ice has a strong control on glacier hydrology